Client satisfaction from the perspective of responsiveness: strategy for analysis of universal systems? - Silvana Martins Mishima; Ana Carolina Campos; Silvia Matumoto; Cinira Magali Fortuna (Universidade de São Paulo, 2016)
Objective: to analyze patient satisfaction in a Family Health Unit (FHU) of a municipality in the interior of São Paulo, Brazil, from the perspective of responsiveness. Method: this was a qualitative study with 41 patients of families who used the FHU at least once in the last six months. A semi-structured interview was used for data collection, performed from November of 2010 to January of 2011, focusing on the dimensions of responsiveness: dignity, autonomy, facilities and physical environment, immediate attention, choice, confidentiality, and communication. A thematic analysis was conducted. Results: four themes emerged from the analysis: the health unit environment; access and components of accessibility - favoring the responsiveness?; possibilities of developing a patient - health service staff relationship; and the FHU team - processing care and welcoming. Conclusion: responsiveness allows for the tracking and monitoring of non-medical aspects of care of the patients; it contributes to achieving universal coverage, emphasizing the quality of care.